Paraphrasing Techniques and Challenges in EFL Academic Writing: Evidence from Indonesian University Students - Alsa Dzulhijayani Ali; Mujahidah Mujahidah; Zulfah Fakhruddin; Maghdahalena Tjalla (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This study investigates paraphrasing techniques, quality, and challenges in EFL academic writing among undergraduate students at IAIN Parepare, Indonesia. Adopting a qualitative approach, data were collected from a paraphrasing test and semi-structured interviews involving 19 English Education students. The analysis integrates Pieterick’s framework of paraphrasing strategies, Keck’s taxonomy of paraphrasing quality, and Shi’s model of learner challenges, supported by thematic coding using NVivo 15. The findings reveal that semantic strategies, particularly synonym substitution, are the most dominant technique (42%), indicating students’ reliance on surface-level transformations. In terms of quality, the majority of students (84%) fall into the Moderate Revision category, suggesting partial modification with limited structural and conceptual transformation. The study also identifies linguistic and cognitive challenges as the primary constraints, including limited vocabulary and difficulties in comprehending and reconstructing meaning from source texts. These findings demonstrate that paraphrasing is a complex cognitive-linguistic process shaped by the interaction between language proficiency and higher-order thinking skills. The study contributes to the literature by proposing an integrated perspective that links paraphrasing strategies, quality, and learner challenges within a unified analytical framework. Pedagogically, the findings highlight the need for instructional approaches that move beyond synonym substitution toward developing critical reading, vocabulary expansion, and idea restructuring skills to support more effective and original academic writing.